Answer:
Step-by-step explanation:
4). Ca(NO₃)₂ + Na₂SO₄ → CaSO₄ + 2Na(NO₃)₂
This question is incorrect.
Since, the final product by reacting Na⁺⁺ and NO₃⁻⁻ is NaNO₃
Correct equation will be,
Ca(NO₃)₂ + Na₂SO₄ → CaSO₄ + 2NaNO₃
This equation is in the balanced form.
5). Ni(NO₃)₂ + KI → NiI + 2K(NO₃)₂
Correct equation will be,
Ni(NO₃)₂ + KI → NiI₂ + 2KNO₃
[Since final product by reacting Ni⁺⁺ and I⁻ is NiI₂]
Balanced form of this equation will be,
Ni(NO₃)₂ + 2KI → NiI₂ + 2KNO₃
6). Ni(NO₃)₂ + KOH → NiOH + K(NO₃)₂
Correct form of the equation will be
Ni(NO₃)₂ + KOH → Ni(OH)₂ + KNO₃
[Since reaction of Ni⁺⁺ and OH⁻ gives Ni(OH)₂ and the reaction of K⁺ and NO₃⁻ gives KNO₃]
Now balancing this equation,
Ni(NO₃)₂ + KOH → Ni(OH)₂ + 2KNO₃
↓
Ni(NO₃)₂ + 2KOH → Ni(OH)₂ + 2KNO₃